Scams, Cons, Frauds, and Deceptions - Byrne, Sean (Victims & offenders, 2023)
The following Thematic Issue presents new research on the nature and extent of a wide range of scams, cons, frauds, and deceptive activities, including sextortion, the use of ransomware, phishing, identity theft, Ponzi schemes, online shopping fraud, gift card scams, and health care fraud targeting elderly victims. Are Americans particularly vulnerable to these scams? And does the public actually admire individuals who get involved, in large part due to the positive portrayal of scammers, fraudsters, and con artists in both literature and cinema? The potential impact of literary and cinematic depictions of these scams on the public’s view of both offending and victimization are considered, along with the government’s ongoing attempts to censure a wide range of books and films that may influence the public’s view of morality–and more recently, the public’s view of our government– due to their content.